Keutamaan kalimah Laa Ilaha Illa Allah di dalam kitab Tanqihul Qoul karya Syaikh Nawawi Al-Bantani perspektif studi Agama Islam - Marjuki, Ismail (Maliki Interdisciplinary Journal, 2023)
Ulama ushul Fiqh defines that hadith is everything that has been based on the prophet in the form of words, deeds, or silence (taqrirnya). Among the books of sheikh Nawawi al-Bantani is the Book of Tanqihul Qoul al-Hatsits bi Syarhi Lubab al-Hadist. This is a book that he wrote through the syarh book of Jalaluddin al-Suyuti, namely the book of Lubab Al-Hadist. He reviewed the book again because in the book Lubab Al-Hadith many reductions or deviations (tahrif) were found. This study uses a descriptive qualitative method using a read-write technique. Technical Analysis of research data in the form of data reduction, data display, and conclusion. This research serves as a reinforcement and reinforces previous research by taking research objectives in the form of: discussion of Fadhilah laa Ilaha Illallah in the Book of Tanqihul Qoul by sheikh Nawawi al-Bantani from the perspective of Islamic religious studies. In the five hadiths in the chapter on the virtues of the sentence laa ilaha illaalah there are virtues including the sentence laa ilaha illahallah as a fortress from Allah’s torment, and our faces shining like the moon in the afterlife.